Influence Human Resources Management Practice to Intention to Stay with Job Satisfaction as a Mediation Variable (Study on Coffee Plus Order Employees) - Putri, Okky Amalia; Rumijati, Aniek; Marsudi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The study was conducted with the aim of knowing the influence of Human Resources Management Practice (HRMP) on Intention to stay (ITS) with job satisfaction as its mediating variable, on Pesen Kopi Plus's employees. The method used in this study is descriptive analytics observation, with cross sectional approaches. Used a sample of 78 respondents with data sources obtained from primary data in the form of questionnaires. Then data analysis techniques regarding scale ranges and Partial Least Square (PLS), using quantitative research and path analysis with Smart PLS. The results of the study showed that Human Resources Management Practice (HRMP) had a significant and positive effect on Intention to stay (ITS). Human Resources Management Practice (HRMP) has a significant and positive effect on job satisfaction. Similarly, job satisfaction has a significant and positive effect on Intention to stay (ITS). In addition, job satisfaction proves a significant influence and mediates the relationship between Human Resources Management Practice (HRMP) and Intention to Stay (ITS).